Mainstreaming Regional Budget (APBD): Issues and Challenges in Riau Province in 2015 - Yandra, Alexsander; Nasution, Sri Roserdevi; Harsini, Harsini; Wekke, Ismail Suardi (Jurnal Politik Indonesia: Indonesian Political Science Review, 2018)
This research explores issues related to mainstreaming the 2015 Regional Budget (APBD) of Riau Province amounted IDR 10.7 trillion. Based on the data obtained from the Riau Finance and Asset Management Board (BPKAD), Riau could only spend APBD 37.58% of APBD until October 2015. Meanwhile, the Ministry of Home Affairs of the Republic of Indonesia calculated Riau spent only 59.6% throughout 2015 and it wast the lowest regional spending in Indonesia. This poor expenditure rate demonstrates a problem in the implementation of Riau’s APBD which was inneficient and not yet relevant. An assessment by government expenditure theory reveals that these problems indicate a gap in APBD allocation that affect on the non-performance regional development as targeted in mid-term regional development plan (RPJMD). This APBD seems to perform only a budget plan, not an implemented budget policy yet.